The Mediating Effect of Financial Analyst Forecasts on the Relationship between Corporate Social Responsibility Disclosure and Investment Efficiency - QIUJIN, ZHAO (Conscientia Beam, 2025)
This study highlights a phenomenon that has received increasing attention in recent years, namely, corporate social responsibility disclosure and investment efficiency. However, previous research rarely explores the transmission mechanism between corporate social responsibility disclosure and investment efficiency, especially how financial analyst forecasts affect this relationship, which is the primary motivation of this study. In reality, Chinese corporate investment activities exhibit high inefficiency, and information asymmetry is one of the main reasons. Corporate social responsibility disclosure provides incremental information to stakeholders. However, there are still a range of challenges to transparency in corporate social responsibility disclosure. Whether financial analysts, as external monitors, play a mediating role in the connection between corporate social responsibility disclosure and investment efficiency is worth studying. Prior research on CSR disclosure has included studies of mandatory social responsibility disclosure policies and CSR disclosure after policy implementation. Therefore, based on 25,552 observations of Chinese listed firms over the period from 2006 to 2022, divided into two samples, this study investigates the mediating role of financial analyst forecasts between corporate social responsibility (CSR) disclosure and investment efficiency. The first sub-sample of 5,442 observations, selected between 2006 and 2011, aims to examine the mediating effect of financial analyst forecasts on the relationship between mandatory corporate social responsibility disclosure and investment efficiency in the short-term effect of mandatory CSR disclosure. The second sub-sample of 24,235 observations, for the period from 2008 to 2022, is selected to investigate the effect of CSR disclosure and its quality on investment efficiency in the long-term effect of mandatory CSR disclosure predicted by financial analysts. Specifically, this sub-sample is used to investigate the mediating role of financial analyst forecasts on the relationship between corporate social responsibility disclosure and investment efficiency, and determine the mediating effect of financial analysts on the relationship between corporate social responsibility disclosure quality and investment efficiency. This study employs panel fixed effects regression modeling of mediation effects using Stata17 software to test this causal inference. The analysis includes difference-in-differences (DID), parallel trend test, placebo test, propensity score matching and difference models (PSM-DID), and bootstrap test. The theoretical foundation of this study is built upon signaling theory, reputation theory, stakeholder theory, and information asymmetry theory. The results indicate that financial analyst forecasts do not play a mediating role in the short-run effects of implementing mandatory social responsibility disclosure policy. However, analysis of the long-term effects of mandatory disclosure policy reveals that companies that disclose social responsibility information, compared to those that do not, can indirectly enhance investment efficiency through analyst forecasts. Financial analyst forecasts do not impact investment efficiency through the quality of CSR disclosure. The study provides that mandatory CSR disclosure policies are effective in the long run, supporting the need to continuously promote and strengthen CSR disclosure policies. The study also highlights the role of financial analysts as key information intermediaries, offering insights for investors, regulators, and policymakers regarding the long-term effects of CSR disclosure transparency on investment decision-making.